2018
DOI: 10.18632/oncotarget.25847
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase HERC1 controls the ERK signaling pathway targeting C-RAF for degradation

Abstract: The RAF/MEK/ERK cascade is a conserved intracellular signaling pathway that controls fundamental cellular processes including growth, proliferation, differentiation, survival and migration. Aberrant regulation of this signaling pathway has long been associated with human cancers. A major point of regulation of this pathway occurs at the level of the serine/threonine protein kinase C-RAF. Here, we show how the E3 ubiquitin ligase HERC1 regulates ERK signaling. HERC1 knockdown induced cellular proliferation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…HERC1 regulates p38 signaling. We have previously shown that the ubiquitin E3 ligase HERC1 regulates the RAF/MEK/ERK signaling pathway 8 . We wondered whether HERC1 might also regulate other MAPK pathways.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HERC1 regulates p38 signaling. We have previously shown that the ubiquitin E3 ligase HERC1 regulates the RAF/MEK/ERK signaling pathway 8 . We wondered whether HERC1 might also regulate other MAPK pathways.…”
Section: Resultsmentioning
confidence: 99%
“…HERC1 has previously been characterized as a ubiquitin E3 ligase regulating the ERK signaling pathway in cell proliferation 8 . Here, we provide the first evidence that HERC1 also acts as a regulator of the p38 signaling pathway, and that this regulation is mediated by the MAPK kinase MKK3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the signaling cluster, ubiquitination also emerged as a distinct functional cluster with isoform-specific interactors ( Figure 5C). SEPT9_i1 associated with HERC1, an E3 ubiqutin ligase that degrades the proto-oncogene serine/threonine-protein kinase c-RAF (110).…”
Section: Functional Clustering Of the Sept9 Proteome Points To Isoformentioning
confidence: 99%